The subaltern’s voice in the literature of Marcelino Freire - Renato Lima de Oliveira; Jacques Fux (Raído, 2013)
This article analyses the representation of the subaltern in the literature of the Brazilian writer Marcelino Freire. We argue that Freire portrays the marginalized with a radical individuality, speaking for themselves and rejecting paternalism. We advance this interpretation by way of a contextualized reading of some of the short-stories present in two of his books: “Contos Negreiros” and “Rasif – mar que arrebenta”. Analytical categories from postcolonial, subaltern and libertarian theories are used to show how Freire mixes historical context, social disparities and individual motivation of subaltern, thus creating a displacement of the hegemony and agency of the marginalized.